Metal-free σ-bond metathesis in 1,3,2-diazaphospholene-catalyzed hydroboration of carbonyl compounds - Chong, Che Chang (2015)
The first metal-free catalytic hydroboration of carbonyl derivatives has been developed in which a catalytic amount of 1,3,2-diazaphospholene effectively promotes a hydroboration reaction of aliphatic and aromatic aldehydes and ketones. The reaction mechanism involves the cleavage of both the P-O bond of the alkoxyphosphine intermediate and the B-H bond of pinacolborane as well as the formation of P-H and B-O bonds. Thus, the reaction proceeds through a non-metal σ-bond metathesis. Kinetic and computational studies suggest that the σ-bond metathesis occurred in a stepwise but nearly concerted manner.